2011
DOI: 10.1002/joc.2101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of East Asian winter monsoon on rainfall over southeastern China and its dynamical process

Abstract: The present study investigates the impact of the East Asian winter monsoon (EAWM) on winter (January, February, and March, or JFM in short) rainfall over southeastern China (including South China and central eastern China) and its dynamical process by using station observations for the period 1951-2003 and the ERA-40 reanalysis for the period 1958-2002. It is found that there is a significant correlation between interannual variations of the EAWM and JFM rainfall over southeastern China. Analyses show that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 39 publications
7
59
0
1
Order By: Relevance
“…The weakened EAWM further weakens the control of its related cold-dry air over East Asia, favouring the northward flow of warm-moist air from low latitudes and the ocean. Consequently, in a weaker EAWM year, there is more winter precipitation over China, in particular over southern China [22,23]. These results are consistent with the distribution of winter precipitation and extreme precipitation associated with climate warming in China.…”
Section: Summary and Discussionsupporting
confidence: 65%
“…The weakened EAWM further weakens the control of its related cold-dry air over East Asia, favouring the northward flow of warm-moist air from low latitudes and the ocean. Consequently, in a weaker EAWM year, there is more winter precipitation over China, in particular over southern China [22,23]. These results are consistent with the distribution of winter precipitation and extreme precipitation associated with climate warming in China.…”
Section: Summary and Discussionsupporting
confidence: 65%
“…Increased dry season rainfall in NET was found to be consistent with wider on-going climate dynamics observed in East Asia and explained by the weakening of the East Asian winter monsoon (Zhou, 2011). These changes were attributed to global warming (Zhang et al, 2011), indicating that rainfall is likely to continue increasing in the future.…”
Section: Discussionsupporting
confidence: 70%
“…Most studies on the effect of ENSO on East Asian summer rainfalls concentrated on spring and summer. However, the effect of ENSO on East Asian rainfall is not limited to summer only (Zhang et al 1999;Wang et al 2000;Chen et al 2009;Zhou and Wu 2010;Zhou 2011). Zhang and Sumi (2002) reported that positive precipitation anomalies were strengthened in winter (December-January-February) in southern regions of China during the El Niño mature phase.…”
Section: Introductionmentioning
confidence: 99%